Relationship of Mandibular Ramus Dimensions to Lower Third Molar Impaction - Al-Gunaid, Talat Hasan; Bukhari, Abdul Kadir; El Khateeb, Sara M.; Yamaki, Masaki (European Journal of Dentistry, 2019)
Objectives The aim of this study was to investigate the mandibular ramus features that could contribute to the etiology of mandibular third molar impaction.Materials and Methods Two hundred and forty subjects were divided into two groups: impacted group: 115 subjects presented with an impacted mandibular third molar, and control group: 125 subjects with the normal mandibular third molar eruption. Digital panoramic radiographs were used, and four angular and twelve linear measurements were done. Comparisons between groups were done using Student's t-test. Pearson correlation and linear regression tests were used to assess the degree of relationship between retromolar space and mandibular measurements.Results Control group showed significant greater measurements in most of the variables, whereas the impacted group showed significant larger gonial angle and larger inclination of lower posterior teeth than the control group. Significant correlations were found between retromolar space and coronoid height, ramal heights, ramus notch depths, the inclination of lower posterior teeth, and retromolar space/3M width ratio in both groups.Conclusion The present study found that the configuration of the mandibular ramus appears to be discrete in many aspects in the erupted other than impacted lower third molars subjects, which might be a possible cause for the impaction.
Keywords: ramal dimensions; lower third molar; impaction